Government and administration: public service and public servants - Gray, Andrew; Jenkins, Bill (2005)
Selected developments in government and administration in 2004 are reviewed. The focus is in turn on the Cabinet and machinery of government, public spending, Parliament and accountability, the civil service and the development of public services. The review suggests that in practice both public services and public servants have changed substantially. The former, although still determined through the political process, are provided through a myriad of forms. The latter, although still committed to the provision of public goods, are as multifaceted as the systems of provision they sustain. It might be, however, that the benefits of current efforts to develop capacity and skills may be realised more effectively by integrating public servants into a common public service. - Reproduced.
Keywords: Public administration - Great Britain; Civil service - Great Britain; Civil service